A Metal-Only ECO Algorithm for Improving Hardware Security with Gate Camouflaging - Su, Liang-Ying; Huang, Shih-Hsu (IEEE International Conference on Consumer Electronics-China (Online), 2023)
Gate camouflaging is a useful method to protect integrated circuits from reverse engineering attacks. However, the design flow for the adoption of gate camouflaging has not been well studied. In this paper, we use camouflaged cells as spare cells. Then, a metal-only ECO (engineering change order) algorithm is proposed to maximize the hardware security by replacing normal cells with camouflaged cells under the same clock period constraint. Experiment results consistently show that the proposed ECO approach can effectively improve the hardware security without violating any timing constraint.